Synergistic Anti-inflammatory and Neuroprotective Effects of Cinnamomum cassia and Zingiber officinale Alleviate Diabetes-Induced Hippocampal Changes in Male Albino Rats: Structural and Molecular Evidence - ALmohaimeed, Hailah M.; Mohammedsaleh, Zuhair M.; Batawi, Ashwaq H.; Balgoon, Maha Jameal; Ramadan, Osama Ibrahim; Baz, Hasan Ahmed; Al Jaouni, Soad; Ayuob, Nasra Naeim (Frontiers in Cell and Developmental Biology, 2021)
Background: Depression has been reported as a common comorbidity in diabetes mellitus although the underlying mechanism responsible for this is not well known. Although both ginger and cinnamon has anti-diabetic, antioxidant, and neuroprotective properties, their efficacy in inhibiting neuroinflammation, when simultaneously administrated, has not been investigated yet. Objectives: The study was designed to assess the synergistic effect of Cinnamomum cassia and Zingiber officinale on regulating blood glucose, improve hippocampal structural changes and depressive-like alternations in diabetic rats, and try to identify the mechanism behind this effect. Materials and Methods: Thirty male Sprague–Dawley rats were divided into five equal groups (n = 6): the normal control, untreated streptozotocin (STZ)-diabetic, cinnamon-treated diabetic [100 mg/kg of body weight (BW)/day for 6 weeks], ginger-treated diabetic (0.5 g/kg BW/day for 6 weeks), and ginger plus cinnamon-treated diabetic groups. Forced swim test and elevated plus maze behavioral tests were performed at the end of the experiment. HOMA-IR, HOMA β-cells, blood glucose, insulin, corticosterone, pro-inflammatory cytokines tumor necrosis factor-α (TNF-α) and IL-6), and total anti-oxidant capacity (TAC) were assessed in the serum. BDNF mRNA level was assessed in hippocampus using qRT-PCR. Hippocampal histopathological changes were also assessed, and immunoexpression of glial fibrillary acidic protein (GFAP), caspase-3, and Ki-67 was measured. Results: Diabetes-induced depressive-like changes in the STZ group were biochemically confirmed by assessing serum corticosterone level, as well as behaviorally using FST and EPM tests. Diabetes also induced degenerative changes in the hippocampus. Treatment of diabetic rats with ginger, cinnamon, or the combination of these alleviated the degenerative structural changes and significantly up-regulated serum insulin, TAC, hippocampal BDNF mRNA, and hippocampal immunoexpression of ki67, while they significantly reduced serum blood glucose, IL-6, TNF-α, IL1β, as well as hippocampal immunoexpression of GFAP and Caspase-3 compared to the untreated diabetic group. Improvement induced by the combination of ginger and cinnamon was superior to the single administration of either of these. Conclusion:Cinnamomum cassia and Zingiber officinale have synergistic anti-diabetic, antioxidant, anti-inflammatory, antidepressant-like, and neuroprotective effects. The use of a combination of these plants could be beneficial as alternative or complementary supplements in managing DM and decreasing its neuronal and psychiatric complications.